Behaviour of angle steel frame confined concrete columns under axial compression. (30th April 2020) - Rong, Chong; Shi, Qingxuan
Highlights: A new kind of composite columns with an outer angle steel frame and an inner concrete column studied in this paper. Confinement mechanism of angle steel frame investigated via theoretical analysis and experimental research. Assembly of steel slabs, size of steel batten and angle steel bar, can characterize the behaviour of ASFCs. Bearing capacity model of ASFCs and the constitutive model of ASF confined concrete proposed in this paper. Abstract: Angle steel frame confined concrete columns (ASFCs) are an emerging form of composite columns. An ASFC consists of a concrete column and an encased angle steel frame. The section form of ASFCs can greatly play steel property on confining core concrete. Existing studies on ASFCs, however, have been rather few and limited. This paper presents a combined experimental and theoretical study on the mechanical properties of ASFCs and the confined concrete under axial compression. The experimental program included the testing of a total of 12 specimens, with the main variables being the concrete strength, the size of angle steel bar and steel batten, the assembly of steel batten. The theoretical part included the confining mechanism of angle steel frame (ASF), bearing capacity model of ASFCs and the constitutive model of ASF confined concrete. The experimental results showed that the angle steel frame can provide well confining effect to confine the core concrete. The proposed model was shown to provide reasonably accurate predictions of the experimental results.